The Role of Customer Satisfaction in Mediating the Effects of Product Quality and Perceived Price Fairness on Switching Intention: A Study of iPhone Users in Denpasar - Kusumaningrum, Ni Wayan Lia; Rahanatha, Gede Bayu (International Journal of Management Science and Information Technology, 2026)
The premium smartphone market has become increasingly competitive, encouraging consumers to evaluate alternative brands based on the value they receive from product performance and pricing. Although the iPhone is widely recognised for its premium positioning, users may still develop intentions to switch when they perceive that the product quality or price no longer provides satisfactory value. This study examines the direct effects of product quality and perceived price fairness on switching intention, while also investigating the mediating role of customer satisfaction among iPhone users in Denpasar. A quantitative approach was adopted by collecting data from 144 respondents selected through purposive sampling. The proposed research model was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The empirical findings indicate that both product quality and perceived price fairness significantly decrease switching intention while simultaneously exerting positive effects on customer satisfaction. In addition, customer satisfaction partially mediates the relationships between product quality and switching intention and between perceived price fairness and switching intention. These findings suggest that consumers are less likely to consider alternative smartphone brands when they perceive superior product quality and fair pricing, as these perceptions strengthen overall satisfaction. From a managerial perspective, the results highlight the importance of continuously enhancing product quality and implementing pricing strategies that consumers perceive as equitable in order to reinforce customer satisfaction and minimise switching intention.